Adolescent and youth participation : adults get ready : two (Commonwealth Secretariat LondonGB, 2005)
Describes roles adults can play in creating an enabling environment for adolescents' participation. Presents ideas and tools for preparing adults to take on these roles.
Keywords: DECISION MAKING